Cassava: the root that unites South with South - International Center for Tropical Agriculture (2015)
Cassava is grown by small farmers in more than 100 tropical and subtropical countries. In Southeast Asia, it is the principal source of calories for vulnerable populations in Cambodia, Laos, and Myanmar. In Vietnam, the crop generates major export earnings, amounting to US$1.1 billion in 2013 for 3.1 million tons of cassava sold for industrial use. Most of the exported roots were supplied by small farmers. This promising global scenario is overshadowed by the spread of witches’-broom disease, which is putting at risk the livelihoods of the approximately 40 million small farmers in Southeast Asia who depend on cassava.